The Relation Between Insider‐Trading Restrictions and Executive Compensation - Roulstone, Darren T. (Journal of Accounting Research, 2003)
abstract In this study I investigate the relation between firm‐level insider‐trading restrictions and executive compensation. Using a trading‐window proxy for the existence of such restrictions, I test predictions that insiders will demand compensation for these restrictions and that firms will need to increase incentives to restricted insiders. I find that firms that restrict insider trading pay a premium in total compensation relative to firms not restricting insider trading, after controlling for economic determinants of pay. Furthermore, these firms use more incentive‐based compensation and their insiders hold larger equity incentives relative to firms that do not restrict insider trading. These results hold after controlling for the endogenous decision to restrict insiders and are consistent with the notion that insider trading plays a role in rewarding and motivating executives.